Analysis of the state order and budget expenses for its funding - Chentsov, Victor; Hryhorash, Olha; Hryhorash, Tetiana (Technology audit and production reserves, 2021)
The object of the research is the budget expenditures for the state order funding. One of the most problematic places is, on the one hand, the lack of financial resources, and on the other hand, the low efficiency of their allocation. Using the method of vertical and horizontal analysis, the expenditures of the consolidated budget for higher education are explored by the example of Ukraine. It was found that the share of the consolidated budget of Ukraine for higher education in % of GDP is one of the largest in Europe, however, the amount of funding is insignificant in monetary terms, which makes it impossible to improve the quality of higher education. The amount of the state order for training of specialists and expenditures of the consolidated budget are analyzed. On the basis of the results of the analysis of the legislation, the impact of elements of the system of formation and state order placement on its effectiveness is assessed. During 2012–2020, the consolidated budget expenditures tended to increase (except for the crisis of 2020, when there was a general economic growth disruption). At the same time, the number of budget places reduced annually until 2018. The analysis of the system of the state order allocation showed that during 2012–2020 it had been changed several times. The main advantages and disadvantages of the system of state order allocation at the stages of its transformation are identified in the paper. Until 2015 the state order allocation was carried out manually. Since 2017 a mechanism for state order addressing has been introduced. In 2020 the mechanism of cost allocation between higher education institutions was changed and indicative prices were introduced. Due to the analysis of the conditions of state order allocation and cost allocation between higher education institutions, it is possible to take into account the main factors that contribute and block the efficiency and effectiveness of funding the higher education system in Ukraine